Hedonism or self-growth? The influence of perceived control on individual product preferences for individuals under self-threat. Issue 6 (4th September 2019) - Zhao, Taiyang; Song, Wei; Jin, Xiaotong; Cui, Hongjing; Li, Yang
Abstract : Purpose: The purpose of this paper is to study the influence of perceived control on product preferences of consumers under self-threat. Design/methodology/approach: By conducting four experiments, this paper manipulated the participants' self-threat and three sources of perceived control – namely, the controllability of the threat itself, the internal and external locus of control of the individual and priming the existing positive or negative experience of the individuals. After the manipulations, the participants' product preferences for self-growth goods or hedonic goods were measured. Findings: The findings of this research indicated that when consumers have a higher perceived control of the threats they are facing, they are more likely to adopt problem-focused coping strategies and show a preference for self-growth goods, which can help them resolve their threats. However, when consumers have a lower perceived control on the threats they are facing, they are more likely to adopt emotion-focused coping strategies and show a preference for hedonic goods, which can help them adjust their emotions. Originality/value: This paper systematically confirms the interactive effect of perceived control and self-threat on consumers' product preferences, as well as the meditation role of problem-focused coping and emotion-focused coping. It also provides insights for marketers to know what factors may affect consumers' preferences for products in self-threat situations, thus contributing to marketing practices.